Impact of an insect growth regulator on the development and the reproduction potency of mosquito - Bouaziz, A; Khedidja, A; Djeghader, N.E; Aïssaoui, L; Boudjelida, H. (My University, 2017)
Mosquitoes are medically and veterinary important vectors, responsible for the transmission of many human and animal diseases, such as malaria, yellow fever, dengue and West Nile Fever [1]. The management of disease vectors using conventional neurotoxic pesticides has failed because of the high reproductive ability, development of insecticide resistance of insect species and secondary effects on none target organisms and environment [2]. These reasons are leading the scientists to focus on the search of novel molecules without secondary effects. They proposed the insect growth regulators (I.G.Rs) as new pesticide alternative, that seem to be promising because of their specific mode of action on insects and their lower toxicity against non-target organisms; specially vertebrate, than conventional insecticides [3, 4, 5]. In the last decades, the I.G.Rs compounds have shown promising results in controlling insects of agricultural, medical and veterinary field [6, 7, 8]. Culex pipiens (Diptera, Culicidae) is the most widely distributed mosquito in the world and carries a number of diseases [9]. According to its large distribution, this represents the most interesting mosquito species in Algeria, particularly in urban areas and is generally controlled by conventional insecticides [10]. The disease spread depends directly on insect vector population and consequently, production of eggs by the insect could be a potential target for vector control. Therefore, the purpose of this study was to evaluate in laboratory, the effectiveness of an insect growth regulator, RH-0345, after treatment during the fourth instar larvae of the domestic mosquito Culex pipiens, and to provide better insights in the physiology of its mode of action.